2020
DOI: 10.1002/ana.25944
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Thickness Predicts the Risk of Cognitive Decline in Parkinson Disease

Abstract: Objective This study was undertaken to analyze longitudinal changes of retinal thickness and their predictive value as biomarkers of disease progression in idiopathic Parkinson's disease (iPD). Methods Patients with Lewy body diseases were enrolled and prospectively evaluated at 3 years, including patients with iPD (n = 42), dementia with Lewy bodies (n = 4), E46K‐SNCA mutation carriers (n = 4), and controls (n = 17). All participants underwent Spectralis retinal optical coherence tomography and Montreal Cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 45 publications
3
43
0
Order By: Relevance
“…3 Interestingly, a recent study has shown that the reduction in the ganglion cell-inner plexiform layer and peripapillary retinal nerve fiber layer thickness over 3 years was related to cognitive decline, but not motor deterioration, in patients with PD. 43 In this study, CNFD had prognostic value for motor deterioration because it is a more stable measure of proximal nerve degeneration, whereas CNFL, CNBD, and CTBD are more variable due to ongoing distal nerve regeneration. 8 Indeed, our previous study showed a decrease in CNFD but an increase in CNBD and CNFL in PD.…”
Section: Discussionmentioning
confidence: 71%
“…3 Interestingly, a recent study has shown that the reduction in the ganglion cell-inner plexiform layer and peripapillary retinal nerve fiber layer thickness over 3 years was related to cognitive decline, but not motor deterioration, in patients with PD. 43 In this study, CNFD had prognostic value for motor deterioration because it is a more stable measure of proximal nerve degeneration, whereas CNFL, CNBD, and CTBD are more variable due to ongoing distal nerve regeneration. 8 Indeed, our previous study showed a decrease in CNFD but an increase in CNBD and CNFL in PD.…”
Section: Discussionmentioning
confidence: 71%
“…It is known that PD patients develop hallucinations, changes in eye and eyelid movement, and altered tear composition and in reduced amounts [ 8 , 9 ]. In addition to eye-surface damage, these patients can experience changes in accommodation, reduced visual acuity, scotoma formation (areas where their field of vision is partially diminished or completely degenerated) and a thinning of the retinal layers, particularly due to a reduction in the number of nerve fibers [ 10 , 11 ]. Deficiencies in neurotransmission and monoamine metabolism also influence the pathological changes to the visual system of PD patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Retinal atrophy seems to be specific to the inner retinal layers, concretely, to macular ganglion cell-inner plexiform complex (GCIPL) around the fovea ( Murueta-Goyena et al, 2019 ), where the largest amount of retinal dopaminergic cells is found ( Ortuño-Lizarán et al, 2020 ). The GCIPL thinning is significantly more pronounced in PD patients over time compared to controls ( Murueta-Goyena et al, 2021 ), but it is present from prodromal stages ( Lee et al, 2019a , b ), suggesting that an early but active neurodegeneration takes place in PD retina ( Murueta-Goyena et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence shows that subjects with mild cognitive impairment (MCI) display retinal vascular network impairment ( Chua et al, 2020 ; Criscuolo et al, 2020 ; Shin et al, 2021 ). Similarly, it seems that PD patients with GCIPL atrophy might constitute a clinical endophenotype with more pronounced cognitive impairment and worse prognosis ( Murueta-Goyena et al, 2019 , 2021 ). However, the relationship between the cognitive status, retinal microvascular parameters and retinal layer thicknesses has not been fully explored in PD patients.…”
Section: Introductionmentioning
confidence: 99%